2012
DOI: 10.2147/ijn.s26141
|View full text |Cite
|
Sign up to set email alerts
|

Preventing postoperative abdominal adhesions in a rat model with PEG-PCL-PEG hydrogel

Abstract: Background: Poly (ethylene glycol)-poly (ε-caprolactone)-poly (ethylene glycol) (PEG-PCL-PEG, PECE) hydrogel has been demonstrated to be biocompatible and thermosensitive. In this study, its potential efficacy and mechanisms of preventing postsurgical abdominal adhesions were investigated. Results: PECE hydrogel was transformed into gel state from sol state in less than 20 seconds at 37°C. None of the animals treated with the hydrogel (n = 15) developed adhesions. In contrast, all untreated animals (n = 15) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Barrier adjuvants are used to prevent adhesions by decreasing the apposition of injured visceral and parietal peritoneum until remesothelialization occurs [ 29 ]. The ideal barrier should not only be anti-adhesive, biocompatible, absorbable, and able to be applied through the laparoscope, but also should remain in place on the traumatized surfaces without sutures or staples, including bleeding surfaces, and not interfere with remesothelialization [ 32 ]. For many years, polymers have been used in the conception of adjuvant barriers including solid membranes, hydrogels or solutions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Barrier adjuvants are used to prevent adhesions by decreasing the apposition of injured visceral and parietal peritoneum until remesothelialization occurs [ 29 ]. The ideal barrier should not only be anti-adhesive, biocompatible, absorbable, and able to be applied through the laparoscope, but also should remain in place on the traumatized surfaces without sutures or staples, including bleeding surfaces, and not interfere with remesothelialization [ 32 ]. For many years, polymers have been used in the conception of adjuvant barriers including solid membranes, hydrogels or solutions [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal adhesions generally begin to be formed in the early postoperative period. Various agents against fibrinous adhesion formation have been tried with promise results in animal models ( 8 ). Along with these findings, observed incidence of postoperative adhesion-related intestinal obstruction after visceral organ transplantation has remained very low ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Postsurgically-activated macrophages release various substances such as cyclooxygenase and lipooxygenase metabolites, plasminogen activator, plasminogen activator-inhibitor, IL-1, IL-6, TNFalpha and collagenase [1,4]. In the presence of these substances, vascular permeability increases and subsequently adhesion formation starts [5,8]. Furthermore, recent studies have reported that inflammatory reactions also cause adhesion via free oxygen radicals and their metabolites [2].…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptom is chronic abdominal and pelvic pain. Intestinal obstruction and infertility can be observed which may cause a significant loss of the patients' quality of life [3,5]. A second laparotomy for the treatment of adhesions causes enhanced postoperative morbidity and mortality due to the loss of normal anatomical configuration [6].…”
Section: Introductionmentioning
confidence: 99%